Analysis of Code Switching in Novel Entitled’ All That is Lost Between Us - Pasaribu, Irene Jenifer; S.Pd.I.M.A, Madina (ELT (English Language Teaching Prima Journal), 2022)
This thesis entitled " all that is lost between us " by Winna Efendi aims to library research is analysis, to provide information from a book and understand three types also six function spoken codes switch from several dialogues at new personal circumstances. This research argues the switch spoken in this novel it is fun to analyze and understand because there are three codes and six contain functions in the dialogue of the novel. People sometimes switch codes in social domains and it is easy to explain the switch. Researchers used qualitative descriptive research methods. The result showed that there are three types of code tag switching, intra-sentential switching, and inter-sentential switching. The material in this novel have the two most widely used types of code-switching are tag switching 22 data and intra-sentential switching 10 data in the fundamental. Next, it is for functions are Quotations, Addressee Specifications, Interjections, Repetition, Messages Qualifications as well as Personalizations. there are two quantities that have the most a total quotation of 13 data and a personalization of 12 data. Keyword : Code switching, intra-sentential, analysis